(3eNJUQ JdNjU GdeaJGMs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J (B:793(3g`s
(3ChdgG (B:s
(3fMeOc jG ef TQM UOhQfG dJdNjU GdHjGf(B... (3hHYO(B... (3bO TQMJ ajeG eVi JdNjU GdeaJGM(B... (3Ke QCjJ(B... (3GNJUGQg hGdGbJUGQ(B...s
(3BNQgG (B:s
(3hcdGeg SHMGfg hJYGdi aj GdQJH GdYdjG ef GdHdGZI hGdZGjI GdbUhi ef GdaUGMI(B... (3eTJed Ydi dWa GdaGJMI (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B219s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B849s
(3GdCYdGe(B: (3L(B7(3, U(B219s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B849s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs